DDRE-12. HETEROGENOUS RESPONSE OF IDH-MUTANT AND IDH-WT GLIOMA TO NAMPT INHIBITION. (25th March 2021) - Rahman, Masum; Hirte, Renee; Olson, Ian; Mansour, Moustafa; Ikram, Samar; MunozCasabella, Amanda; Sutiwisesak, Rujapope; Carlstrom, Lucas; Warrington, Arthur; Rajani, Karishma; Sarkaria, Jann; Burns, Terry
Abstract: BACKGROUND: NAD+ is required for cell metabolism and DNA repair. It is generated from nicotinic acid (NA) by NAPRT and from Nicotinamide (NAM) by NAMPT. D2HG in IDH-mutant tumors methylates and inactivates NAPRT, increasing dependence on NAMPT. Toxic side effects of NAMPT inhibition can be prevented by NA supplementation in healthy cells without NAPRT methylation. A1326133 is a recently described CNS-penetrant NAMPT inhibitor hypothesized to selectively eliminate IDH-mutant NAPRT-methylated gliomas, likely in combination with other therapies. Our group is looking for biomarkers of drug efficacy to augment individualized therapies. To that end, we sought to identify GBM cell lines with varying sensitivity to NAMPT inhibition. METHODS: Human non-immortalized astrocytes and human GBM cell lines were utilized from the Mayo Clinic Glioma patient-derived xenograft resource, including IDH-R132Hmutant lines (GBM164, 196) and IDH-WT lines (GBM6, 12, 76). Cell viability was analyzed after 4days incubation with the NAMPT inhibitor, A1326133 +/- Temozolomide (TMZ) or NA. IC50 for A1326133 was estimated based on intracellular ATP using Cell-Titer-Glo. RESULTS: Marked heterogeneity between lines was observed in response to A1326133 +/- NA or TMZ. Sensitive and resistant lines were identified among both IDH-mutant and IDH-WT cell lines. IC50s: GBM164, 12, 6, 196 and 76 were 5.6, 9.3, 39.2, 910, and 9455nM, respectively. NA partially rescued GBM164 by NA (IC50 increased to 20.8nM) but not GBM6 nor 12. IC50 for Human astrocytes was 221.7nM, but >10, 000nM with NA. Addition of TMZ did not improve A1326133 efficacy. CONCLUSION: Our data illustrate the potential utility of NAMPT inhibition to kill a subset of IDH-WT and IDH mutant lines, but conflict with previously reported TMZ synergy and correlation with mutant IDH. NA may increase safety but could decrease efficacy in certain lines. Ongoing studies seek metabolic biomarkers of therapeutic efficacy to guide individualized therapy with NAMPT inhibitors.